2021
DOI: 10.1155/2021/5569410
|View full text |Cite
|
Sign up to set email alerts
|

ACE2 and Apelin-13: Biomarkers with a Prognostic Value in Congestive Heart Failure

Abstract: The progression of heart failure is the result of the interaction of several pathogenetic processes that involve the activation of biomarkers belonging to the renin angiotensin aldosterone system (RAAS), to its counterregulatory mechanisms, to the sympathetic nervous system and inflammation, and to oxidative stress. This study is aimed at determining the prognostic role of biomarkers in the evolution of patients with heart failure. These biomarkers are representative of different pathogenetic pathways involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…With the significant aging of the population, HF has become an important social and public health problem [ 18 ]. Cardiac remodeling is an important pathophysiological process of heart failure, which is related to the interaction of myocardial cell apoptosis, myocardial hypertrophy and myocardial fibrosis [ 19 ]. HF is characterized by a poor prognosis [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the significant aging of the population, HF has become an important social and public health problem [ 18 ]. Cardiac remodeling is an important pathophysiological process of heart failure, which is related to the interaction of myocardial cell apoptosis, myocardial hypertrophy and myocardial fibrosis [ 19 ]. HF is characterized by a poor prognosis [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps several clinical features of HF patients including fatigue, altered physical tolerance, myopathy and cardiac cachexia may be regulated by an altered myokine profile [ 38 ]. Moreover, these myokines were important predictive factors for shortening survival in patients with any HF phenotype [ 39 , 40 , 41 ]. It has been suggested that the metabolic effects of the myokines that contribute to the myocardial–skeletal muscle axis should be regarded as a critical element of T2DM-induced impairment of cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial remodeling in HFpEF differs from myocardial remodeling in HFrEF, which is caused by the death of cardiomyocytes due to oxidative stress caused by various factors such as ischemia, infection, and toxicity ( Figure 1 ) [ 13 , 14 , 15 ].…”
Section: Main Pathophysiological Mechanisms Involved In the Productio...mentioning
confidence: 99%